Mengungkap Hoaks: Memberdayakan Siswa SMP dengan Keterampilan Berpikir Kritis - Abdul Syahid; Dhea Nuraisyah; Widya Wulandari; Sandrina Rizkia Ramadhani; Syafina Annazah; Novita Sari; Muhammad Najmi Al-Habsyi; Ayu Muliahayati Nashir (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
The development of the internet and technology is currently growing so that it provides many benefits but also negative impacts. For children who are still underage, the problem that is often encountered is the spread of fake news or more commonly known as hoaxes. This is the background of this PKM activity to contribute to the community, especially 7th grade students at SMP NU Palangka Raya. This PKM activity aims to teach critical listening and thinking skills to provide a better understanding of the existence of hoaxes, and train students to be more critical in filtering the information they receive. The activity was conducted for 7th grade students with 2 different classes at SMP NU Palangka Raya. This PKM method uses participatory observation. The results of the observation showed that classes 7-1 and 7-2 were active in this service activity. However, class 7-1 was more interactive than class 7-2. This activity makes a positive contribution in shaping a smarter and more critical young generation in the use of social media